CHALLENGES AND POTENTIAL OF ENVIRONMENTAL EDUCATION IN THE PMVA: A SOCIAL NETWORK APPROACH - Veronese, Thábata Biazzuz; Mollo Neto, Mario (Seven Editora, 2026)
Population growth and the advancement of civilization intensify pressure on natural resources, demanding public policies that ensure survival conditions grounded in intergenerational solidarity. In this scenario, environmental education emerges as an essential instrument for the implementation of policies aimed at sustainable development. The Green-Blue Municipality Program (PMVA) acts as a mediator between the municipalities of São Paulo and the State Secretariat for the Environment, promoting actions aimed at improving the quality of life and local and regional sustainability. This proposal analyzes the exchange of information in environmental education through Social Network Analysis (SNA), using the Netdraw® and Ucinet® software to map interactions between municipalities participating in the PMVA. The methodology adopted, of an exploratory and descriptive nature, considers indices and benefits associated with the program, relating them to the UN Sustainable Development Goals (SDGs). The results indicate that the application of SNA in the environmental education sector makes it possible to understand information flows and verify compliance with the program’s criteria. Furthermore, it allows the creation of structural indicators capable of assisting municipalities in increasing their scores, as well as strengthening their capacity to plan, execute, and evaluate educational actions in a continuous and integrated manner, involving schools, the community, and public management. The graphical analysis of the networks reveals a significant disparity between the best-evaluated municipalities and those with lower performance, highlighting challenges in the equity of the implementation of environmental policies. Although the PMVA (Green-Blue Municipality Program) represents a relevant public policy for fostering municipal participation in favor of sustainable development, the results demonstrate that there are still necessary advances to fully achieve the proposed objectives.